Effect of Strengthening on the Fatigue Life of Construction Materials - Brzeziński, Karol; Zbiciak, Artur; Garbacz, Andrzej (Periodica Polytechnica Civil Engineering, 2019)
The paper describes a new method for assessing the impact of increasing static strength due to cyclic loading on the fatigue life of various materials and provides a mathematical description. Experimental results available in the literature were used. A generalized concept of unit fatigue damage was used to produce a simple hypothesis defining fatigue life as a function of load history. The method is mainly devoted to analysis of semi-rigid asphalt pavements but can also be applied to other engineering materials. Two sample calculations were conducted which drew on the results of fatigue tests under variable loading: one concerns cement-treated soils used as base layers for road pavements and the second describes the fatigue problem of a beam rear axle made of TL1114.